(untitled) (Revista Médica de Trujillo, 2026)
Objetive: To determine the efficacy of early intratympanic corticosteroid therapy in improving hearing in patients with sudden idiopathic sensorineural hearing loss treated at the Almanzor Aguinaga Asenjo Hospital from 2010 to 2019. Methods: A retrospective cohort study was conducted in patients with sensorineural hearing loss aged 18 to 59 years. A sample of 37 patients who received early corticosteroid therapy and 37 patients who received late corticosteroid therapy were included. Their medical records were reviewed, and chi-square, relative risk, and analysis of variance were applied. Results: The average increase in decibel level in patients who received early therapy was 5.9 dB (95% CI: 1.81-9.92) greater than in those who received late therapy, with p=0.005. Likewise, in those who received early therapy, the probability of hearing improvement increased by 60% (95% CI: 1-154%) compared to those who received late therapy. Conclusions: Early intratympanic corticosteroid therapy was more effective than late therapy, as patients were more likely to experience hearing improvement in both decibels and percentage frequency.